Gallium nitride single crystal wafer and its preparation method and application

By setting up a stress covariant layer during the preparation of the gallium nitride single wafer, stress decoupling is achieved, and the problem of large lattice mismatch and thermal mismatch stress coordination is solved, and large-size crack-free, warp-free low-stress gallium nitride single wafers were successfully prepared.

CN118727136BActive Publication Date: 2025-03-25INST OF SEMICONDUCTORS - CHINESE ACAD OF SCI +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411114498.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2025-03-25
Estimated Expiration
2044-08-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively coordinate the large lattice mismatch and thermal mismatch stress during the preparation of gallium nitride single wafers, resulting in undulations, warping and cracks of the film layer, limiting the preparation of large-size self-supported gallium nitride single wafers.

Method used

By setting up a stress covariant layer, weak bond decoupling effect is formed, large-sized gallium nitride single crystal chips are prepared. The specific method includes preparing a multi-layer epitaxial layer on a silicon single crystal substrate and annealing treatment to form a porous aluminum oxide and a magnesium oxide stress covariant layer to achieve stress decoupling.

Benefits of technology

The preparation of large-size gallium nitride single wafers is achieved, avoiding the ups and downs, warping and cracking of the film layer, improving the yield and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118727136B_ABST
    Figure CN118727136B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a gallium nitride single crystal wafer, which can be applied to the field of semiconductor technology. The method comprises: preparing a silicon single crystal substrate; preparing a first epitaxial layer on the silicon single crystal substrate by a pulsed magnetron sputtering process; completely thermally decomposing and separating the zinc component in the first epitaxial layer by an in-situ annealing process to obtain a second epitaxial layer; epitaxially growing a gallium nitride single crystal thin film template layer on the second epitaxial layer by a pulsed magnetron sputtering process; lowering the temperature to room temperature at a first preset cooling rate; growing a gallium nitride single crystal thick film epitaxial layer on the gallium nitride single crystal thin film template layer by a vapor phase epitaxial process; lowering the temperature to room temperature at a second preset cooling rate; and peeling the gallium nitride single crystal thick film epitaxial layer from other parts, and processing the gallium nitride single crystal thick film epitaxial layer to obtain a gallium nitride single crystal wafer. The present invention also provides a gallium nitride single crystal wafer and its application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of semiconductor technology, and in particular to a gallium nitride single crystal wafer and a preparation method and application thereof. Background Art

[0002] It is difficult to prepare and grow large-sized bulk single crystal materials of wide bandgap semiconductor material gallium nitride (GaN) by melting or solution method. At present, sapphire substrate or silicon single crystal substrate is usually used to prepare GaN. Among them, the preparation of GaN on sapphire substrate usually uses metal organic chemical vapor deposition (MOCVD) heteroepitaxial to prepare a flat surface GaN single crystal thin film template layer, and then uses hydride vapor phase epitaxy (HVPE) secondary epitaxial rapid growth to reduce dislocation density. This method usually only uses a simple strong bonded aluminum nitride single crystal film or low-temperature GaN film as a buffer layer to regulate stress, which is difficult to effectively coordinate large lattice mismatch (16%) stress and large thermal mismatch (-34%) stress. The thicker the film layer, the greater the accumulated stress and it is mainly compressive stress, which not only causes the film layer to fluctuate and warp, but also causes the film layer to crack when the accumulated stress release reaches a certain critical thickness (crack-free thickness). This is also one of the reasons why the yield rate of large-sized self-supporting GaN single crystal thick film materials prepared using sapphire single crystal substrates is low and the price is always expensive. Compared with sapphire substrate, heteroepitaxial preparation using silicon single crystal substrate can realize the preparation of larger size gallium nitride single crystal thick film materials, but the large mismatch stress problem caused by heteroepitaxial preparation of gallium nitride single crystal thick film materials using silicon single crystal substrate material is more serious (lattice mismatch -16.9%, thermal mismatch 56%, silicon diffusion and serious interface reaction problems). In addition, since the thermal expansion coefficient of silicon substrate is much smaller than that of gallium nitride, greater tensile stress will be generated during the substantial cooling process after the completion of high-temperature MOCVD or HVPE preparation and growth. It is still difficult to increase the crack-free thickness of the gallium nitride epitaxial film on silicon substrate of not less than 4 inches to more than 5µm by using the currently commonly used strongly bonded aluminum nitride single crystal film as a barrier layer and nucleation layer, and then preparing a multi-layer strongly bonded aluminum component gradient aluminum gallium nitride (AlGaN) stress covariant layer or inserting a multi-period gallium nitride / aluminum nitride (GaN / AlN) superlattice insertion layer. Because of this, there is no research or production report on the use of silicon substrates of not less than 4 inches to prepare crack-free self-supporting gallium nitride single crystal thick film materials with a thickness of more than 100µm. Therefore, the use of large-size silicon single crystal substrates and MOCVD and HVPE to achieve the preparation of large-size self-supporting gallium nitride single crystal materials is an urgent problem to be solved, which requires the design of new stress control structures and the development of new methods. Summary of the invention

[0003] 1. Technical issues to be resolved

[0004] In order to solve at least one of the above-mentioned technical problems arising in the preparation process of gallium nitride single crystal wafers in the prior art, an embodiment of the present invention provides a gallium nitride single crystal wafer and a preparation method and application thereof. By setting a stress covariant layer to form a weak bonding decoupling effect, the upper and lower large thermal mismatch stresses generated in the preparation process can be transferred to the middle respectively, so as to prepare a large-sized gallium nitride single crystal wafer.

[0005] (II) Technical solution

[0006] In view of the above technical problems, embodiments of the present invention provide a gallium nitride single crystal wafer and a preparation method and application thereof.

[0007] According to a first aspect of the present invention, a method for preparing a gallium nitride single crystal wafer is provided, comprising the following steps: preparing a silicon single crystal substrate; preparing a first epitaxial layer on the silicon single crystal substrate by a pulsed magnetron sputtering process; completely thermally decomposing and separating the zinc component in the first epitaxial layer by an in-situ annealing process to obtain a second epitaxial layer; epitaxially growing a gallium nitride single crystal thin film template layer on the second epitaxial layer by a pulsed magnetron sputtering process; lowering the temperature to room temperature at a first preset cooling rate to obtain a crack-free, low-stress gallium nitride single crystal thin film template layer that is weakly bonded and decoupled from the silicon single crystal substrate; growing a gallium nitride single crystal thick film epitaxial layer on the gallium nitride single crystal thin film template layer by a vapor phase epitaxial process; and growing the gallium nitride single crystal thick film epitaxial layer on the gallium nitride single crystal thin film template layer by a second preset cooling rate. The temperature is lowered to room temperature at a cooling rate so that the gallium nitride single crystal thick film epitaxial layer is completely peeled off from the silicon single crystal substrate; the other parts are peeled off from the gallium nitride single crystal thick film epitaxial layer, and the gallium nitride single crystal thick film epitaxial layer is processed to obtain a gallium nitride single crystal wafer, wherein the first epitaxial layer includes an aluminum nitride single crystal thin film barrier layer, a first aluminum zinc oxide polycrystalline thin film layer, a magnesium zinc oxide polycrystalline thin film layer, a second aluminum zinc oxide polycrystalline thin film layer and an aluminum nitride polycrystalline thin film layer arranged in sequence; and the second epitaxial layer includes an aluminum nitride single crystal thin film barrier layer, a first porous aluminum oxide stress covariant layer, a porous magnesium oxide stress covariant layer, a second porous aluminum oxide stress covariant layer and an aluminum nitride single crystal thin film nucleation layer arranged in sequence.

[0008] In some exemplary embodiments, preparing a silicon single crystal substrate includes: baking the silicon single crystal substrate to remove the oxide layer remaining on the surface and adsorbed impurities, wherein the baking temperature is 800° C.-900° C.

[0009] In some exemplary embodiments, a pulsed magnetron sputtering process is used to prepare a first epitaxial layer on a silicon single crystal substrate, including: adjusting the heating temperature to 650°C-750°C, using a high-purity metal aluminum target as a target material, high-purity nitrogen as a reaction gas, and high-purity argon as a sputtering gas, and using a reactive pulsed DC magnetron sputtering single target sputtering deposition process to form an aluminum nitride single crystal thin film barrier layer on a silicon single crystal substrate; adjusting the heating temperature to 550°C-650°C, using high-purity metal aluminum and high-purity metal zinc as targets, high-purity oxygen as a reaction gas, and high-purity Argon is used as sputtering gas, and reactive pulsed DC magnetron sputtering double targets are used for co-sputtering deposition to form a first aluminum zinc oxide polycrystalline thin film layer on the aluminum nitride single crystal thin film barrier layer, wherein the first aluminum zinc oxide polycrystalline thin film layer has a single C-axis preferred orientation, and the molar concentration of zinc element in the first aluminum zinc oxide polycrystalline thin film layer is 30%-50%; the heating temperature is adjusted to 450°C-550°C, high-purity metal magnesium and high-purity metal zinc are used as target materials, high-purity oxygen is used as reaction gas, and high-purity argon is used as sputtering gas, and reactive pulsed DC magnetron sputtering double targets are used for co-sputtering deposition. A co-sputtering deposition process is used to form a magnesium zinc oxide polycrystalline thin film layer on the first aluminum zinc oxide polycrystalline thin film layer, wherein the magnesium zinc oxide polycrystalline thin film layer has a single C-axis preferred orientation, and the molar concentration of zinc in the magnesium zinc oxide polycrystalline thin film layer is 65%-85%; the heating temperature is adjusted to 550°C-650°C, high-purity metal aluminum and high-purity metal zinc are used as target materials, high-purity oxygen is used as a reaction gas, and high-purity argon is used as a sputtering gas, and a reactive pulsed DC magnetron sputtering double-target co-sputtering deposition process is adopted to form a second aluminum zinc oxide polycrystalline thin film layer on the magnesium zinc oxide polycrystalline thin film layer. A polycrystalline aluminum zinc oxide thin film layer is formed on the second aluminum zinc oxide polycrystalline thin film layer, wherein the second aluminum zinc oxide polycrystalline thin film layer has a single C-axis preferred orientation, and the molar concentration of zinc element in the second aluminum zinc oxide polycrystalline thin film layer is 30%-50%; and the heating temperature is adjusted to 650° C.-750° C., high-purity metallic aluminum is used as a target material, high-purity nitrogen is used as a reaction gas, and high-purity argon is used as a sputtering gas, and a reactive pulsed DC magnetron sputtering single-target sputtering deposition process is adopted to form an aluminum nitride polycrystalline thin film layer on the second aluminum zinc oxide polycrystalline thin film layer, wherein the aluminum nitride polycrystalline thin film layer has a single C-axis preferred orientation.

[0010] In some exemplary embodiments, an in-situ annealing process is used to completely thermally decompose and precipitate the zinc component in the first epitaxial layer to obtain a second epitaxial layer, including: adjusting the heating temperature to 850°C-950°C, annealing the first epitaxial layer in a hydrogen atmosphere for 0.5h-5h to decompose the zinc component in the first aluminum zinc oxide polycrystalline thin film layer, the magnesium zinc oxide polycrystalline thin film layer, and the second aluminum zinc oxide polycrystalline thin film layer and precipitate from the grain gaps and grain boundaries in the aluminum nitride polycrystalline thin film layer to form a first porous aluminum oxide stress covariant layer, a porous magnesium oxide stress covariant layer, and a second porous aluminum oxide stress covariant layer having different nanoporosities; and adjusting the heating temperature to 1000°C-1200°C, annealing in an ammonia atmosphere for 1h-10h to fuse and recrystallize the grains in the aluminum nitride polycrystalline thin film layer to form an aluminum nitride single crystal thin film nucleation layer, wherein the dislocation density of the aluminum nitride single crystal thin film nucleation layer is not higher than 1×10 9 cm -2 , and the surface flatness of the aluminum nitride single crystal thin film nucleation layer is not higher than 1.0 nm.

[0011] In some exemplary embodiments, a pulsed magnetron sputtering process is used to epitaxially grow a gallium nitride single crystal thin film template layer on the second epitaxial layer, including: adjusting the heating temperature to 700°C-900°C, using high-purity liquid metal gallium as a target material, high-purity nitrogen as a reaction gas, and high-purity argon as a sputtering gas, and using reactive pulsed DC magnetron sputtering single target sputtering deposition to form a gallium nitride single crystal thin film template layer on the aluminum nitride single crystal thin film nucleation layer, wherein the gallium nitride single crystal thin film template layer has a single C-axis preferred orientation.

[0012] In some exemplary embodiments, a gallium nitride single crystal thick film epitaxial layer is grown on a gallium nitride single crystal thin film template layer using a vapor phase epitaxial process, including: adjusting a heating temperature to 1000° C.-1100° C., and using a near-normal pressure hydride vapor phase epitaxy process to epitaxially grow the gallium nitride single crystal thick film epitaxial layer.

[0013] In some exemplary embodiments, the first preset temperature drop rate is not less than 10° C. / min; and / or the second preset temperature drop rate is not less than 15° C. / min.

[0014] In some exemplary embodiments, at least one of the following features is included: the thickness of the silicon single crystal substrate is 300µm-1500µm; the thickness of the aluminum nitride single crystal thin film barrier layer is 300nm-500nm; the thickness of the first aluminum zinc oxide polycrystalline thin film layer is 30nm-50nm; the thickness of the magnesium zinc oxide polycrystalline thin film layer is 20nm-30nm; the thickness of the second aluminum zinc oxide polycrystalline thin film layer is 30nm-50nm; the thickness of the aluminum nitride polycrystalline thin film layer is 300nm-500nm; the thickness of the gallium nitride single crystal thin film template layer is 1000nm-5000nm; the thickness of the gallium nitride single crystal thick film epitaxial layer is 500μm-5000µm.

[0015] According to a second aspect of the present invention, a gallium nitride single crystal wafer is provided. The gallium nitride single crystal wafer is prepared by the above method.

[0016] According to a third aspect of the present invention, there is provided an application of a gallium nitride single crystal wafer prepared by the above method, which can be applied to at least one of gallium nitride-based power electronic devices, gallium nitride-based microwave radio frequency devices, gallium nitride-based light emitting diode devices, gallium nitride-based laser diode devices and gallium nitride-based ultraviolet detection devices.

[0017] (III) Beneficial effects

[0018] It can be seen from the above technical solutions that the gallium nitride single crystal wafer and its preparation method and application provided by the embodiments of the present invention have at least the following beneficial effects:

[0019] (1) Based on the design of a thin aluminum nitride single crystal film barrier layer strongly bonded to a silicon single crystal substrate and a thin aluminum nitride single crystal film nucleation layer strongly bonded to a gallium nitride single crystal film template layer, a first porous aluminum oxide stress-covariant layer and a second porous aluminum oxide stress-covariant layer are designed and prepared respectively. Due to the in-plane thermal expansion coefficient of aluminum oxide (7.5×10 -6 K -1 ) is smaller than the in-plane thermal expansion coefficient of silicon single crystal substrate (3.59×10 -6 K -1 ) and the thermal expansion coefficient of the GaN epitaxial layer (5.59×10 -6 K -1 ) is large. Although the nanoporosity of the first porous alumina stress covariant layer and the second porous alumina stress covariant layer is low, there is still a certain degree of weak bond decoupling effect, which can realize the transition of the upper and lower large thermal mismatch stresses generated during the large cooling process to the middle.

[0020] (2) A porous magnesium oxide stress-covariant layer with high nanoporosity is designed and prepared in the middle. Due to the thermal expansion coefficient of magnesium oxide (9.84×10 -6 K -1 ) is larger than alumina, and shrinks more during a large temperature drop. The large thermal tensile stress generated by the silicon single crystal substrate and the gallium nitride epitaxial layer can be transferred to this layer through the first porous alumina stress covariant layer and the second porous alumina stress covariant layer for concentrated release, resulting in more obvious weak bond decoupling here, further blocking the upward transfer and transmission of the tensile stress generated by the silicon single crystal substrate.

[0021] (3) By regulating the nanoporosity and thickness of the porous magnesium oxide stress-covariant layer and controlling the cooling rate, the GaN single crystal thick film can be completely self-peeled off from the large-size silicon single crystal substrate during the final cooling process.

[0022] (4) By adopting a step-by-step annealing process, the zinc component is first thermally decomposed and completely precipitated by high-temperature and high-vacuum annealing in a hydrogen atmosphere to form a multi-layer porous stress covariant layer containing nanopores, thereby achieving weak bonding decoupling between the first porous aluminum oxide stress covariant layer and the aluminum nitride single crystal film barrier layer, and weak bonding decoupling between the second porous aluminum oxide stress covariant layer and the aluminum nitride polycrystalline film layer; on the basis of this weak bonding decoupling, annealing is performed again, which makes it easier to achieve the fusion and recrystallization of the grains in the aluminum nitride polycrystalline film layer to form a high-crystalline quality aluminum nitride single crystal film nucleation layer. It is more conducive to the preparation of high-crystalline quality, smooth surface, low-stress gallium nitride single crystal film template layer and gallium nitride single crystal thick film epitaxial layer.

[0023] (5) The present invention adopts a pulsed DC sputtering process and an in-situ annealing process to prepare an aluminum nitride single crystal thin film barrier layer, a porous aluminum oxide stress covariance layer, a porous magnesium oxide stress covariance layer, an aluminum nitride single crystal thin film nucleation layer and a gallium nitride single crystal thin film template layer. Compared with the commonly used MOCVD equipment, the equipment cost is low and it is easy to mass produce.

[0024] (6) The present invention utilizes the process characteristics of a medium-high temperature reactive pulsed DC magnetron sputtering process to facilitate the growth of high-quality single crystals of aluminum nitride and gallium nitride films. The medium-high temperature reactive pulsed DC magnetron sputtering process is first used to achieve the preparation and growth of high-quality single crystals of aluminum nitride films with a single C-axis preferred orientation on a silicon single crystal substrate. The barrier layer can not only effectively block the silicon atoms decomposed at high temperature on the surface of the silicon substrate from diffusing into the subsequently prepared epitaxial layers, but also provide a good growth template for the subsequent polycrystalline growth of the first aluminum zinc oxide film layer, the magnesium zinc oxide film layer, the second aluminum zinc oxide film layer and the aluminum nitride film layer with a single C-axis preferred orientation prepared in sequence by the medium-low temperature pulsed DC magnetron sputtering process. The prepared aluminum nitride polycrystalline film layer with a single C-axis preferred orientation provides sufficient grain gaps and grain boundary channels for the subsequent in-situ annealing in a hydrogen atmosphere to separate out the zinc component decomposed in each of the first aluminum zinc oxide polycrystalline film layer, the magnesium zinc oxide polycrystalline film layer and the second aluminum zinc oxide polycrystalline film layer containing zinc components. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The above contents and other objects, features and advantages of the present invention will become more apparent through the following description of the embodiments of the present invention with reference to the accompanying drawings, in which:

[0026] Figure 1 A schematic diagram of a process of preparing a gallium nitride single crystal wafer according to an embodiment of the present invention is schematically shown;

[0027] Figure 2 A schematic diagram of the structure after a first epitaxial layer is prepared on a silicon single crystal substrate by using a pulsed magnetron sputtering process according to an embodiment of the present invention is shown;

[0028] Figure 3 A schematic diagram of the structure after the zinc component in the first epitaxial layer is completely thermally decomposed and separated out by an in-situ annealing process to obtain a second epitaxial layer according to an embodiment of the present invention is shown; and

[0029] Figure 4 The schematic diagram shows a structure diagram before and after the temperature is lowered to room temperature at a second preset cooling rate according to an embodiment of the present invention, wherein: Figure 4 (a) schematically shows a structural schematic diagram before the temperature is lowered to room temperature at a second preset cooling rate; Figure 4 (b) schematically shows a schematic diagram of the structure after the temperature is reduced to room temperature at a second preset cooling rate; and

[0030] Figure 5 The structural diagram of a gallium nitride single crystal wafer according to an embodiment of the present invention is schematically shown.

[0031] Reference numerals:

[0032] 1-silicon single crystal substrate; 2-first epitaxial layer; 21-aluminum nitride single crystal thin film barrier layer; 22-first aluminum zinc oxide polycrystalline thin film layer; 23-magnesium zinc oxide polycrystalline thin film layer; 24-second aluminum zinc oxide polycrystalline thin film layer; 25-aluminum nitride polycrystalline thin film layer; 3-second epitaxial layer; 31-first porous aluminum oxide stress covariant layer; 32-porous magnesium oxide stress covariant layer; 33-second porous aluminum oxide stress covariant layer; 34-aluminum nitride single crystal thin film nucleation layer; 4-gallium nitride single crystal thin film template layer; 5-gallium nitride single crystal thick film epitaxial layer; 6-gallium nitride single crystal wafer. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in combination with specific embodiments and with reference to the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] In the embodiments of the present invention, a variety of high-purity substances are used, among which the mass fraction of aluminum element in high-purity metallic aluminum is greater than 99.99%; the mass fraction of magnesium element in high-purity metallic magnesium is greater than 99.99%; the mass fraction of zinc element in high-purity metallic zinc is greater than 99.99%; the mass fraction of nitrogen element in high-purity nitrogen is greater than 99.99%; the mass fraction of argon element in high-purity argon is greater than 99.99%; and the mass fraction of gallium element in high-purity liquid metallic gallium is greater than 99.99%.

[0035] Figure 1The flowchart of a method for preparing a gallium nitride single crystal wafer according to an embodiment of the present invention is schematically shown.

[0036] like Figure 1 As shown, a method for preparing a gallium nitride single crystal wafer according to an embodiment of the present invention includes steps S110-S180.

[0037] In step S110 , a silicon single crystal substrate 1 is prepared.

[0038] In some exemplary embodiments, step S110 includes baking the silicon single crystal substrate 1 to remove the oxide layer and adsorbed impurities remaining on the surface, wherein the baking temperature is 800° C.-900° C. Optionally, the thickness of the silicon single crystal substrate 1 is 300µm-1500µm. Optionally, the size of the silicon single crystal substrate includes a diameter of 2 inches, 4 inches, 6 inches, 8 inches, and 12 inches.

[0039] For example, a silicon single crystal substrate 1 with a thickness of 300µm-1500µm is prepared, placed in a growth chamber of a magnetron sputtering device with a maximum substrate heating temperature of not less than 1200°C, the substrate heating temperature is raised to 800°C-900°C, and the silicon single crystal substrate 1 is baked at high temperature and high vacuum to completely remove the residual oxide layer and adsorbed impurities on the surface.

[0040] In step S120, a pulsed magnetron sputtering process is used to prepare a first epitaxial layer 2 on a silicon single crystal substrate 1. The first epitaxial layer 2 includes an aluminum nitride single crystal thin film barrier layer 21, a first aluminum zinc oxide polycrystalline thin film layer 22, a magnesium zinc oxide polycrystalline thin film layer 23, a second aluminum zinc oxide polycrystalline thin film layer 24 and an aluminum nitride polycrystalline thin film layer 25, which are arranged in sequence. Figure 2 .

[0041] In some exemplary embodiments, step S120 includes:

[0042] The heating temperature is adjusted to 650° C.-750° C., a high-purity metal aluminum target is used as a target material, high-purity nitrogen is used as a reaction gas, and high-purity argon is used as a sputtering gas, and a reactive pulsed DC magnetron sputtering single target is used for sputtering deposition to form an aluminum nitride single crystal thin film barrier layer 21 on a silicon single crystal substrate 1. Optionally, the thickness of the aluminum nitride single crystal thin film barrier layer 21 is 300nm-500nm.

[0043] The heating temperature is adjusted to 550°C-650°C, high-purity metal aluminum and high-purity metal zinc are used as target materials, high-purity oxygen is used as reaction gas, and high-purity argon is used as sputtering gas. A reactive pulsed DC magnetron sputtering double-target co-sputtering deposition process is adopted to form a first aluminum zinc oxide polycrystalline film layer 22 on the aluminum nitride single crystal film barrier layer 21, wherein the first aluminum zinc oxide polycrystalline film layer 22 has a single C-axis preferred orientation, and the molar concentration of zinc element in the first aluminum zinc oxide polycrystalline film layer 22 is 30%-50%. Optionally, the thickness of the first aluminum zinc oxide polycrystalline film layer 22 is 30nm-50nm.

[0044] The heating temperature is adjusted to 450°C-550°C, high-purity metal magnesium and high-purity metal zinc are used as target materials, high-purity oxygen is used as reaction gas, and high-purity argon is used as sputtering gas, and a reactive pulsed DC magnetron sputtering double-target co-sputtering deposition process is adopted to form a magnesium zinc oxide polycrystalline film layer 23 on the first aluminum zinc oxide polycrystalline film layer 22, wherein the magnesium zinc oxide polycrystalline film layer 23 has a single C-axis preferred orientation, and the molar concentration of zinc element in the magnesium zinc oxide polycrystalline film layer 23 is 65%-85%. Optionally, the thickness of the magnesium zinc oxide polycrystalline film layer 23 is 20nm-30nm.

[0045] The heating temperature is adjusted to 550°C-650°C, high-purity metal aluminum and high-purity metal zinc are used as target materials, high-purity oxygen is used as reaction gas, and high-purity argon is used as sputtering gas. A reactive pulsed DC magnetron sputtering double-target co-sputtering deposition process is adopted to form a second aluminum zinc oxide polycrystalline film layer 24 on the magnesium zinc oxide polycrystalline film layer 23, wherein the second aluminum zinc oxide polycrystalline film layer 24 has a single C-axis preferred orientation, and the molar concentration of zinc element in the second aluminum zinc oxide polycrystalline film layer 24 is 30%-50%. Optionally, the thickness of the second aluminum zinc oxide polycrystalline film layer 24 is 30nm-50nm.

[0046] The heating temperature is adjusted to 650° C.-750° C., high-purity metal aluminum is used as a target material, high-purity nitrogen is used as a reaction gas, and high-purity argon is used as a sputtering gas. A reactive pulsed DC magnetron sputtering single target sputtering deposition process is adopted to form an aluminum nitride polycrystalline film layer 25 on the second aluminum zinc oxide polycrystalline film layer 24, wherein the aluminum nitride polycrystalline film layer 25 has a single C-axis preferred orientation. Optionally, the thickness of the aluminum nitride polycrystalline film layer 25 is 300nm-500nm.

[0047] In step S130, the zinc component in the first epitaxial layer 2 is completely thermally decomposed and separated by an in-situ annealing process to obtain a second epitaxial layer 3. The second epitaxial layer 3 includes an aluminum nitride single crystal thin film barrier layer 21, a first porous aluminum oxide stress covariant layer 31, a porous magnesium oxide stress covariant layer 32, a second porous aluminum oxide stress covariant layer 33 and an aluminum nitride single crystal thin film nucleation layer 34, which are arranged in sequence. Figure 3 .

[0048] In some exemplary embodiments, step S130 includes adjusting the heating temperature to 850° C.-950° C., and annealing the first epitaxial layer 2 for 0.5 h-5 h in a hydrogen atmosphere to decompose the zinc component in the first aluminum zinc oxide polycrystalline thin film layer 22, the magnesium zinc oxide polycrystalline thin film layer 23, and the second aluminum zinc oxide polycrystalline thin film layer 24 and precipitate from the grain gaps and grain boundaries in the aluminum nitride polycrystalline thin film layer 25 to form a first porous aluminum oxide stress covariant layer 31, a porous oxide layer 32, and a second porous oxide layer 33 having different nanoporosities. The aluminum nitride polycrystalline film layer 25 is formed by forming a magnesium stress covariant layer 32 and a second porous aluminum oxide stress covariant layer 33, and realizing weak bonding decoupling between the aluminum nitride polycrystalline film layer 25 and the aluminum nitride single crystal film barrier layer 21; and adjusting the heating temperature to 1000° C.-1200° C., annealing for 1 h-10 h in an ammonia atmosphere, so as to fuse and recrystallize the grains in the aluminum nitride polycrystalline film layer 25 to form an aluminum nitride single crystal film nucleation layer 34, wherein the dislocation density of the aluminum nitride single crystal film nucleation layer 34 is not higher than 1×10 9 cm -2 , and the surface flatness of the aluminum nitride single crystal thin film nucleation layer 34 is not higher than 1.0 nm.

[0049] In step S140 , a gallium nitride single crystal thin film template layer 4 is epitaxially grown on the second epitaxial layer 3 by using a pulsed magnetron sputtering process.

[0050] In some exemplary embodiments, step S140 includes adjusting the heating temperature to 700° C.-900° C., using high-purity liquid metal gallium as a target material, high-purity nitrogen as a reaction gas, and high-purity argon as a sputtering gas, and adopting reactive pulsed DC magnetron sputtering single target sputtering deposition to form a gallium nitride single crystal thin film template layer 4 on the aluminum nitride single crystal thin film nucleation layer 34, wherein the gallium nitride single crystal thin film template layer 4 has a single C-axis preferred orientation. Optionally, the gallium nitride single crystal thin film template layer 4 has a thickness of 1000nm-5000nm.

[0051] In step S150, the temperature is lowered to room temperature at a first preset cooling rate to obtain a crack-free, low-stress gallium nitride single crystal thin film template layer that is weakly bonded and decoupled from the silicon single crystal substrate. Optionally, the first preset cooling rate is not less than 10°C / min. In the cooling process, the thermal mismatch tensile stress generated by the silicon single crystal substrate 1 and the gallium nitride single crystal thin film template layer 4 is first transferred to the first porous alumina stress covariant layer 31 and the second porous alumina stress covariant layer 33 containing nanopores in the middle, and then concentrated in the porous magnesium oxide stress covariant layer 32 with the highest nanopore density. Release, and take out the crack-free, low-stress gallium nitride single crystal thin film template layer 4 that is weakly bonded and decoupled from the silicon single crystal substrate 1.

[0052] In step S160, a gallium nitride single crystal thick film epitaxial layer 5 is grown on the gallium nitride single crystal thin film template layer 4 by using a vapor phase epitaxy process. Optionally, the gallium nitride single crystal thick film epitaxial layer 5 has a thickness of 500 μm-5000 μm. Figure 4 (a) in the figure.

[0053] In some exemplary embodiments, step S160 includes adjusting the heating temperature to 1000° C.-1100° C. and epitaxially growing the gallium nitride single crystal thick film epitaxial layer 5 using a near-normal pressure hydride vapor phase epitaxy process.

[0054] In step S170, the temperature is lowered to room temperature at a second preset cooling rate so that the gallium nitride single crystal thick film epitaxial layer is completely self-peeled off from the silicon single crystal substrate. Optionally, the second preset cooling rate is not less than 15°C / min. During the cooling process, the thermal mismatch tensile stress generated by the silicon single crystal substrate 1 and the gallium nitride single crystal thick film epitaxial layer 5 is simultaneously transferred to the first porous alumina stress covariant layer 31 and the second porous alumina stress covariant layer 33 containing nanopores in the middle, and then concentrated and released in the porous magnesium oxide stress covariant layer 32 with the highest nanopore density. The temperature is lowered and taken out to obtain a crack-free, warping-free, low-stress, self-supporting gallium nitride single crystal thick film epitaxial layer 5 that is completely self-peeled off from the silicon single crystal substrate 1, having a structure as shown in FIG. Figure 4 In (b), the porous magnesium oxide stress covariant layer 32 breaks during the cooling process.

[0055] In step S180, the other parts are peeled off from the gallium nitride single crystal thick film epitaxial layer 5, and the gallium nitride single crystal thick film epitaxial layer 5 is processed to obtain a gallium nitride single crystal wafer 66, see Figure 5 Optionally, the gallium nitride single crystal thick film epitaxial layer 5 has a thickness of 500 μm-5000 μm.

[0056] For example, the crack-free, warping-free, low-stress self-supporting gallium nitride single crystal thick film epitaxial layer 5 is cut, ground and polished to remove the back surface of the nanoporous porous magnesium oxide stress covariant layer 32, the second porous aluminum oxide stress covariant layer 33, the aluminum nitride single crystal film nucleation layer 34 and the gallium nitride single crystal film template layer 4 with high defect density, and the processing obtains multiple sheets with a thickness of not less than 300 μm and a dislocation density of not more than 1×10 7 cm -2 A crack-free, warp-free, low-stress self-supporting gallium nitride single crystal wafer 6 material with a surface roughness not higher than 0.5 nm.

[0057] The gallium nitride single crystal wafer 6 according to the embodiment of the present invention can be applied to at least one of gallium nitride-based power electronic devices, gallium nitride-based microwave radio frequency devices, gallium nitride-based light emitting diode devices, gallium nitride-based laser diode devices and gallium nitride-based ultraviolet detection devices.

[0058] A gallium nitride single crystal wafer 6 and a preparation method and application thereof provided in an embodiment of the present invention are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the protection scope of the present invention.

[0059] Example 1

[0060] A method for preparing a 6-inch self-supporting gallium nitride single crystal material comprises the following steps:

[0061] S1. Prepare a silicon single crystal substrate 1 with a thickness of 1000 µm, and place it in a growth chamber of a magnetron sputtering device with a maximum substrate heating temperature of 1200°C.

[0062] S2. Raise the substrate heating temperature to 900° C. and perform high-temperature and high-vacuum baking on the 6-inch silicon single crystal substrate 1 to completely remove the residual oxide layer and adsorbed impurities on the surface.

[0063] S3. The substrate heating temperature is adjusted to 700°C. A high-purity metal aluminum target is used as the target material, high-purity nitrogen is used as the reaction gas, and high-purity argon is used as the sputtering gas. Reactive pulsed DC magnetron sputtering single target sputtering deposition is adopted to form a 400nm thick aluminum nitride single crystal thin film barrier layer 21 on the silicon single crystal substrate 1.

[0064] S4. The substrate heating temperature is adjusted to 600°C. High-purity metal aluminum and high-purity metal zinc are used as target materials, high-purity oxygen is used as reaction gas, and high-purity argon is used as sputtering gas. Reactive pulsed DC magnetron sputtering double-target co-sputtering deposition is adopted to form a first aluminum zinc oxide polycrystalline thin film layer 22 with a thickness of 40nm, a zinc element molar concentration of 40% and a single C-axis preferred orientation on the aluminum nitride single crystal thin film barrier layer 21.

[0065] S5. The substrate heating temperature is adjusted to 500° C., and high-purity metal magnesium and high-purity metal zinc are used as target materials, high-purity oxygen is used as reaction gas, and high-purity argon is used as sputtering gas. Reactive pulsed DC magnetron sputtering double-target co-sputtering deposition is adopted to form a magnesium zinc oxide polycrystalline thin film layer 23 with a thickness of 20 nm, a zinc element molar concentration of 70%, and a single C-axis preferred orientation on the first aluminum zinc oxide polycrystalline thin film layer 22.

[0066] S6. Adjust the substrate heating temperature to 600°C, use high-purity metal aluminum and high-purity metal zinc as target materials, high-purity oxygen as reaction gas, and high-purity argon as sputtering gas, and adopt reactive pulse DC magnetron sputtering double-target co-sputtering deposition to form a second aluminum zinc oxide polycrystalline thin film layer 24 with a thickness of 40 nm, a zinc element molar concentration of 40%, and a single C-axis preferred orientation on the magnesium zinc oxide polycrystalline thin film layer 23.

[0067] S7. Adjust the substrate heating temperature to 700°C, use high-purity metal aluminum as the target material, high-purity nitrogen as the reaction gas, and high-purity argon as the sputtering gas, and adopt reactive pulsed DC magnetron sputtering single target sputtering deposition to form an aluminum nitride polycrystalline thin film layer 25 with a thickness of 400nm and a single C-axis preferred orientation on the second aluminum zinc oxide polycrystalline thin film layer 24.

[0068] S8. Adjust the substrate heating temperature to 900°C, and perform high-temperature high-vacuum annealing for 2 hours on the first aluminum zinc oxide polycrystalline thin film layer 22, the magnesium zinc oxide polycrystalline thin film layer 23, and the second aluminum zinc oxide polycrystalline thin film layer 24 in a hydrogen atmosphere, so that the zinc component in the film layer is thermally decomposed and completely precipitated from the grain gaps and grain boundaries in the aluminum nitride polycrystalline thin film layer 25, to form a first porous aluminum oxide stress covariant layer 31, a porous magnesium oxide stress covariant layer 32, and a second porous aluminum oxide stress covariant layer 33 having different nanoporosities, and realize weak bonding decoupling between the aluminum nitride polycrystalline thin film layer 25 and the aluminum nitride single crystal thin film barrier layer 21 and the silicon single crystal substrate 1.

[0069] S9, adjusting the substrate heating temperature to 1100° C., and performing high-temperature high-vacuum annealing for 5 hours on the weakly bonded and decoupled aluminum nitride polycrystalline thin film layer 25 in an ammonia atmosphere, so that the grains in the aluminum nitride polycrystalline thin film layer 25 fuse, merge, and recrystallize to form a dislocation density of no more than 5×10 8 cm -2 The aluminum nitride single crystal thin film nucleation layer 34 has a surface flatness of no more than 1.0 nm.

[0070] S10. Adjust the substrate heating temperature to 800°C, use high-purity liquid metal gallium as the target material, high-purity nitrogen as the reaction gas, and high-purity argon as the sputtering gas, and adopt reactive pulsed DC magnetron sputtering single target sputtering deposition to form a gallium nitride single crystal thin film template layer 4 with a thickness of 3000nm and a single C-axis preferred orientation on the aluminum nitride single crystal thin film nucleation layer 34.

[0071] S11, regulating the first cooling rate to 10°C / min to quickly cool to room temperature. During the cooling process, the thermal mismatch tensile stress generated by the silicon single crystal substrate 1 and the gallium nitride single crystal thin film template layer 4 is first transferred to the first porous alumina stress covariant layer 31 and the second porous alumina stress covariant layer 33 containing nanopores in the middle, and then concentrated and released in the porous magnesium oxide stress covariant layer 32 with the highest nanopore density, and a crack-free and low-stress gallium nitride single crystal thin film template layer 4 that is weakly bonded and decoupled from the silicon single crystal substrate 1 is obtained.

[0072] S12, placing the crack-free, low-stress gallium nitride single crystal thin film template layer 4 that is weakly bonded and decoupled from the silicon single crystal substrate 1 into the reaction chamber of the hydride vapor phase epitaxy equipment, adjusting the substrate heating temperature to 1050°C, and using a near-normal-pressure hydride vapor phase epitaxy process to rapidly epitaxially grow a gallium nitride single crystal thick film epitaxial layer 5 with a thickness of 2000µm.

[0073] S13, regulating the second cooling rate to 15°C / min and rapidly cooling to room temperature. During the cooling process, the thermal mismatch tensile stress generated by the silicon single crystal substrate 1 and the gallium nitride single crystal thick film epitaxial layer 5 is simultaneously transferred to the first porous alumina stress covariant layer 31 and the second porous alumina stress covariant layer 33 containing nanopores in the middle, and then concentrated in the porous magnesium oxide stress covariant layer 32 with the highest nanopore density for release. After cooling, a crack-free, warping-free, low-stress, self-supporting gallium nitride single crystal thick film epitaxial layer 5 is obtained which is decoupled and completely self-peeled from the silicon single crystal substrate 1.

[0074] S14, cutting, grinding and polishing the crack-free, warping-free, low-stress self-supporting gallium nitride single crystal thick film epitaxial layer 5, removing the back surface including the nanoporous porous magnesium oxide stress covariant layer 32, the second porous aluminum oxide stress covariant layer 33, the aluminum nitride single crystal film nucleation layer 34 and the gallium nitride single crystal film template layer 4 with high defect density, and processing to obtain 5 sheets with a thickness of 300µm and a dislocation density of no more than 5×10 6 cm -2 A crack-free, warping-free, low-stress 6-inch self-supporting gallium nitride single crystal wafer 6 material with a surface roughness of no more than 0.5 nm.

[0075] The prepared 6-inch self-supporting gallium nitride single crystal material 6 is used to develop and produce gallium nitride-based power electronic devices.

[0076] Embodiment 2:

[0077] A method for preparing an 8-inch self-supporting gallium nitride single crystal wafer comprises the following steps:

[0078] S1. Prepare a silicon single crystal substrate 1 with a thickness of 1500 µm, and place it in a growth chamber of a magnetron sputtering device with a maximum substrate heating temperature of 1200°C.

[0079] S2. Raise the substrate heating temperature to 900° C. and perform high-temperature and high-vacuum baking on the silicon single crystal substrate 1 to completely remove the residual oxide layer and adsorbed impurities on the surface.

[0080] S3. The substrate heating temperature is adjusted to 750°C. A high-purity metal aluminum target is used as the target material, high-purity nitrogen is used as the reaction gas, and high-purity argon is used as the sputtering gas. Reactive pulsed DC magnetron sputtering single target sputtering deposition is adopted to form a 500nm thick aluminum nitride single crystal thin film barrier layer 21 on the silicon single crystal substrate 1.

[0081] S4. The substrate heating temperature is adjusted to 650°C. High-purity metal aluminum and high-purity metal zinc are used as target materials, high-purity oxygen is used as reaction gas, and high-purity argon is used as sputtering gas. Reactive pulsed DC magnetron sputtering double-target co-sputtering deposition is adopted to form a first aluminum zinc oxide polycrystalline thin film layer 22 with a thickness of 50 nm, a zinc element molar concentration of 50%, and a single C-axis preferred orientation on the aluminum nitride single crystal thin film barrier layer 21.

[0082] S5. The substrate heating temperature is adjusted to 550°C. High-purity metal magnesium and high-purity metal zinc are used as target materials, high-purity oxygen is used as reaction gas, and high-purity argon is used as sputtering gas. Reactive pulsed DC magnetron sputtering double-target co-sputtering deposition is adopted to form a magnesium zinc oxide polycrystalline thin film layer 23 with a thickness of 30 nm, a zinc element molar concentration of 75%, and a single C-axis preferred orientation on the first aluminum zinc oxide polycrystalline thin film layer 22.

[0083] S6. Adjust the substrate heating temperature to 650°C, use high-purity metal aluminum and high-purity metal zinc as target materials, high-purity oxygen as reaction gas, and high-purity argon as sputtering gas, and adopt reactive pulse DC magnetron sputtering double-target co-sputtering deposition to form a second aluminum zinc oxide polycrystalline thin film layer 24 with a thickness of 50 nm, a zinc element molar concentration of 50%, and a single C-axis preferred orientation on the magnesium zinc oxide polycrystalline thin film layer 23.

[0084] S7. Adjust the substrate heating temperature to 750°C, use a high-purity metal aluminum target as the target material, high-purity nitrogen as the reaction gas, and high-purity argon as the sputtering gas, and adopt reactive pulsed DC magnetron sputtering single target sputtering deposition to form an aluminum nitride polycrystalline thin film layer 25 with a thickness of 500nm and a single C-axis preferred orientation on the second aluminum zinc oxide polycrystalline thin film layer 24.

[0085] S8. Adjust the substrate heating temperature to 950°C, and perform high-temperature high-vacuum annealing for 3 hours on the first aluminum zinc oxide polycrystalline thin film layer 22, the magnesium zinc oxide polycrystalline thin film layer 23, and the second aluminum zinc oxide polycrystalline thin film layer 24 in a hydrogen atmosphere, so that the zinc component in the film layer is thermally decomposed and completely precipitated from the grain gaps and grain boundaries in the aluminum nitride polycrystalline thin film layer 25, to form a first porous aluminum oxide stress covariant layer 31, a porous magnesium oxide stress covariant layer 32, and a second porous aluminum oxide stress covariant layer 33 having different nanoporosities, and realize weak bonding decoupling between the aluminum nitride polycrystalline thin film layer 25 and the aluminum nitride single crystal thin film barrier layer 21 and the silicon single crystal substrate 1.

[0086] S9, adjusting the substrate heating temperature to 1100° C., and performing high-temperature high-vacuum annealing for 5 hours on the weakly bonded and decoupled aluminum nitride polycrystalline thin film layer 25 in an ammonia atmosphere, so that the grains in the aluminum nitride polycrystalline thin film layer 25 fuse, merge, and recrystallize to form a dislocation density of no more than 5×10 8 cm -2 The aluminum nitride single crystal thin film nucleation layer 34 has a surface flatness not higher than 1.0 nm.

[0087] S10. Adjust the substrate heating temperature to 800°C, use high-purity liquid metal gallium as the target material, high-purity nitrogen as the reaction gas, and high-purity argon as the sputtering gas, and adopt reactive pulsed DC magnetron sputtering single target sputtering deposition to form a gallium nitride single crystal thin film template layer 4 with a thickness of 5000nm and a single C-axis preferred orientation on the aluminum nitride single crystal thin film nucleation layer 34.

[0088] S11, regulating the first cooling rate to 15°C / min and rapidly cooling to room temperature. During the cooling process, the thermal mismatch tensile stress generated by the silicon single crystal substrate 1 and the gallium nitride single crystal thin film template layer 4 is first transferred to the first porous alumina stress covariant layer 31 and the second porous alumina stress covariant layer 33 containing nanopores in the middle, and then concentrated and released in the porous magnesium oxide stress covariant layer 32 with the highest nanopore density, thereby obtaining a crack-free and low-stress gallium nitride single crystal thin film template layer 4 that is weakly bonded and decoupled from the silicon single crystal substrate 1.

[0089] S12, placing the crack-free, low-stress gallium nitride single crystal thin film template layer 4 that is weakly bonded and decoupled from the silicon single crystal substrate 1 into the reaction chamber of the hydride vapor phase epitaxy equipment, adjusting the substrate heating temperature to 1050°C, and using a near-normal-pressure hydride vapor phase epitaxy process to rapidly epitaxially grow a gallium nitride single crystal thick film epitaxial layer 5 with a thickness of 3000µm.

[0090] S13, regulating the second cooling rate to 20°C / min to quickly cool down to room temperature. During the cooling process, the thermal mismatch tensile stress generated by the silicon single crystal substrate 1 and the gallium nitride single crystal thick film epitaxial layer 5 is simultaneously transferred to the first porous alumina stress covariant layer 31 and the second porous alumina stress covariant layer 33 containing nanopores in the middle, and then concentrated and released in the porous magnesium oxide stress covariant layer 32 with the highest nanopore density. The temperature is lowered to obtain a crack-free, warping-free, low-stress self-supporting gallium nitride single crystal thick film epitaxial layer 5 that is decoupled and completely self-peeled from the silicon single crystal substrate 1.

[0091] S14, cutting, grinding and polishing the crack-free, warping-free, low-stress self-supporting gallium nitride single crystal thick film epitaxial layer 5, removing the back surface including the nanoporous porous magnesium oxide stress covariant layer 32, the second porous aluminum oxide stress covariant layer 33, the aluminum nitride single crystal film nucleation layer 34 and the gallium nitride single crystal film template layer 4 with high defect density, and processing to obtain 5 sheets with a thickness of 400µm and a dislocation density of no more than 5×10 6 cm -2 A crack-free, warping-free, low-stress 8-inch self-supporting gallium nitride single crystal wafer 6 material with a surface roughness not higher than 0.5 nm.

[0092] The prepared 8-inch self-supporting gallium nitride single crystal 6 material is used to develop and produce gallium nitride-based laser diode devices.

[0093] The above specific embodiments further illustrate the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a gallium nitride single crystal wafer, characterized in that: The following steps are involved: preparing a silicon single crystal substrate; preparing a first epitaxial layer on the silicon single crystal substrate by using a pulsed magnetron sputtering process; Using an in-situ annealing process to completely thermally decompose and separate out the zinc component in the first epitaxial layer to obtain a second epitaxial layer; epitaxially growing a gallium nitride single crystal thin film template layer on the second epitaxial layer by using a pulsed magnetron sputtering process; Lowering the temperature to room temperature at a first preset cooling rate to obtain a crack-free, low-stress gallium nitride single crystal thin film template layer that is weakly bonded and decoupled from the silicon single crystal substrate; Growing a gallium nitride single crystal thick film epitaxial layer on the gallium nitride single crystal thin film template layer by using a vapor phase epitaxial process; Lowering the temperature to room temperature at a second preset cooling rate so that the gallium nitride single crystal thick film epitaxial layer is completely self-stripped from the silicon single crystal substrate; and The other parts are peeled off from the gallium nitride single crystal thick film epitaxial layer, and the gallium nitride single crystal thick film epitaxial layer is processed to obtain a gallium nitride single crystal wafer, The first epitaxial layer includes an aluminum nitride single crystal thin film barrier layer, a first aluminum zinc oxide polycrystalline thin film layer, a magnesium zinc oxide polycrystalline thin film layer, a second aluminum zinc oxide polycrystalline thin film layer and an aluminum nitride polycrystalline thin film layer, which are arranged in sequence; and The second epitaxial layer includes an aluminum nitride single crystal thin film barrier layer, a first porous aluminum oxide stress-covariant layer, a porous magnesium oxide stress-covariant layer, a second porous aluminum oxide stress-covariant layer and an aluminum nitride single crystal thin film nucleation layer, which are arranged in sequence. Wherein, the method of preparing the first epitaxial layer on the silicon single crystal substrate by using a pulsed magnetron sputtering process comprises: The heating temperature is adjusted to 650° C.-750° C., a high-purity metal aluminum target is used as a target material, high-purity nitrogen is used as a reaction gas, and high-purity argon is used as a sputtering gas, and a reactive pulsed DC magnetron sputtering single target sputtering deposition process is adopted to form an aluminum nitride single crystal thin film barrier layer on the silicon single crystal substrate; The heating temperature is adjusted to 550° C.-650° C., high-purity metal aluminum and high-purity metal zinc are used as target materials, high-purity oxygen is used as reaction gas, and high-purity argon is used as sputtering gas. A reactive pulsed DC magnetron sputtering double-target co-sputtering deposition process is adopted to form a first aluminum zinc oxide polycrystalline thin film layer on the aluminum nitride single crystal thin film barrier layer, wherein the first aluminum zinc oxide polycrystalline thin film layer has a single C-axis preferred orientation; and the molar concentration of zinc element in the first aluminum zinc oxide polycrystalline thin film layer is 30%-50%; The heating temperature is adjusted to 450° C.-550° C., high-purity metal magnesium and high-purity metal zinc are used as target materials, high-purity oxygen is used as reaction gas, and high-purity argon is used as sputtering gas, and a reactive pulsed DC magnetron sputtering double-target co-sputtering deposition process is adopted to form a magnesium zinc oxide polycrystalline thin film layer on the first aluminum zinc oxide polycrystalline thin film layer, wherein the magnesium zinc oxide polycrystalline thin film layer has a single C-axis preferred orientation; and the molar concentration of zinc element in the magnesium zinc oxide polycrystalline thin film layer is 65%-85%; The heating temperature is adjusted to 550° C.-650° C., and a reactive pulsed DC magnetron sputtering double-target co-sputtering deposition process is adopted using high-purity aluminum and high-purity zinc as target materials, high-purity oxygen as reaction gas, and high-purity argon as sputtering gas to form a second aluminum-zinc-oxygen polycrystalline thin film layer on the magnesium-zinc-oxygen polycrystalline thin film layer, wherein the second aluminum-zinc-oxygen polycrystalline thin film layer has a single C-axis preferred orientation; and the molar concentration of zinc element in the second aluminum-zinc-oxygen polycrystalline thin film layer is 30%-50%; and The heating temperature is adjusted to 650° C.-750° C., and a reactive pulsed DC magnetron sputtering single target sputtering deposition process is adopted using high-purity aluminum as a target material, high-purity nitrogen as a reaction gas, and high-purity argon as a sputtering gas to form an aluminum nitride polycrystalline thin film layer on the second aluminum zinc oxide polycrystalline thin film layer, wherein the aluminum nitride polycrystalline thin film layer has a single C-axis preferred orientation; The method of using an in-situ annealing process to completely thermally decompose and separate out the zinc component in the first epitaxial layer to obtain a second epitaxial layer comprises: Adjusting the heating temperature to 850° C.-950° C., and annealing the first epitaxial layer for 0.5 h-5 h in a hydrogen atmosphere, so as to decompose the zinc components in the first aluminum zinc oxide polycrystalline thin film layer, the magnesium zinc oxide polycrystalline thin film layer, and the second aluminum zinc oxide polycrystalline thin film layer and precipitate them from the grain gaps and grain boundaries in the aluminum nitride polycrystalline thin film layer, to form a first porous aluminum oxide stress-cooperative layer, a porous magnesium oxide stress-cooperative layer, and a second porous aluminum oxide stress-cooperative layer having different nanoporosities; and The heating temperature is adjusted to 1000° C.-1200° C., and annealing is performed in an ammonia atmosphere for 1 h-10 h to fuse and recrystallize the grains in the aluminum nitride polycrystalline thin film layer to form an aluminum nitride single crystal thin film nucleation layer. Wherein, the dislocation density of the aluminum nitride single crystal film nucleation layer is not higher than 1×10 9 cm -2 ;as well as The surface flatness of the aluminum nitride single crystal thin film nucleation layer is not higher than 1.0 nm.

2. The method for preparing a gallium nitride single crystal wafer according to claim 1, characterized in that: The step of preparing a silicon single crystal substrate comprises: The silicon single crystal substrate is baked to remove the oxide layer remaining on the surface and the adsorbed impurities, wherein the baking temperature is 800°C-900°C.

3. The method for preparing a gallium nitride single crystal wafer according to claim 1, characterized in that: The method of epitaxially growing a gallium nitride single crystal thin film template layer on the second epitaxial layer by using a pulsed magnetron sputtering process comprises: The heating temperature is adjusted to 700° C.-900° C., high-purity liquid metal gallium is used as a target material, high-purity nitrogen is used as a reaction gas, and high-purity argon is used as a sputtering gas. A reactive pulsed DC magnetron sputtering single target sputtering deposition process is adopted to form a gallium nitride single crystal thin film template layer on the aluminum nitride single crystal thin film nucleation layer. Wherein, the gallium nitride single crystal thin film template layer has a single C-axis preferred orientation.

4. The method for preparing a gallium nitride single crystal wafer according to claim 1, characterized in that: The method adopts a vapor phase epitaxy process to grow a gallium nitride single crystal thick film epitaxial layer on the gallium nitride single crystal thin film template layer, comprising: The heating temperature is adjusted to 1000° C.-1100° C., and a gallium nitride single crystal thick film epitaxial layer is epitaxially grown using a near-normal-pressure hydride vapor phase epitaxy process.

5. The method for preparing a gallium nitride single crystal wafer according to claim 1, characterized in that: The first preset cooling rate is not less than 10°C / min; and / or The second preset cooling rate is not less than 15°C / min.

6. The method for preparing a gallium nitride single crystal wafer according to claim 1, characterized in that: Includes at least one of the following features: The thickness of the silicon single crystal substrate is 300µm-1500µm; The thickness of the aluminum nitride single crystal thin film barrier layer is 300nm-500nm; The thickness of the first aluminum zinc oxide polycrystalline thin film layer is 30nm-50nm; The thickness of the magnesium zinc oxide polycrystalline thin film layer is 20nm-30nm; The thickness of the second aluminum zinc oxide polycrystalline thin film layer is 30nm-50nm; The thickness of the aluminum nitride polycrystalline thin film layer is 300nm-500nm; The thickness of the gallium nitride single crystal thin film template layer is 1000nm-5000nm; The thickness of the gallium nitride single crystal thick film epitaxial layer is 500 μm-5000 μm.

7. A gallium nitride single crystal wafer, characterized in that: The gallium nitride single crystal wafer is prepared by the method according to any one of claims 1 to 6.

8. An application of a gallium nitride single crystal wafer prepared by the method according to any one of claims 1 to 6, characterized in that: It is applied to at least one of gallium nitride-based power electronic devices, gallium nitride-based microwave radio frequency devices, gallium nitride-based light emitting diode devices, gallium nitride-based laser diode devices and gallium nitride-based ultraviolet detection devices.

Citation Information

Patent Citations

  • Silicon-base compound substrate and manufacturing method thereof

    CN102208337A

  • Method for preparing aluminum nitride single crystal material

    CN102828251A